Marketing Strategy Via Instagram at Hotel Holiday Inn Express Jakarta International Expo - Nicko Gana Saputra; Reza Imani Syawal; Putri, Ni Made Dwiyana Rasuma; Fahira (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This study aims to analyze the room marketing strategy of Holiday Inn Express Jakarta International Expo Hotel using social media. Method: The research employs a qualitative approach, utilizing primary and secondary data. Data collection methods include literature reviews, interviews, and field observations. Descriptive qualitative analysis was used to interpret the findings. Result and Discussion: Observations of the hotel’s Instagram account demonstrate the effectiveness of social media as a marketing tool. Instagram’s billion active users provide extensive promotional opportunities, allowing businesses to engage audiences through images, videos, and stories creatively. Influencers are critical in building trust and expanding product reach, while official accounts manage brand visibility and customer relationships. Instagram Highlights effectively organize and present key messages, fostering cohesive brand narratives. The strategic use of Instagram at Holiday Inn Express Jakarta International Expo emphasizes visuals, personal connections, and guest engagement, proving its effectiveness in boosting brand visibility and enhancing promotional efforts. Implications: The marketing strategies for Holiday Inn Express Jakarta International Expo Hotel involve enhancing product quality and service offerings to increase occupancy rates and revenue. Online marketing, mainly through platforms like Instagram, has become crucial in the hotel’s marketing mix. This involves using electronic media, such as computers and the Internet, to execute digital campaigns effectively. The findings highlight the need for thorough preparation and strategic execution in digital marketing to ensure success in a highly competitive environment.